(untitled) (SCIENCE TIME JOURNAL, 2026)
This study examines the effectiveness of clinical case-based tasks in developing modal competence among future doctors in English for Medical Purposes (EMP). Although medical students often possess foundational knowledge of modal verbs, they frequently struggle to apply them appropriately in authentic clinical communication. To address this issue, a quasi-experimental design was employed involving control and experimental groups of second-year medical students. While the control group received traditional grammar-focused instruction, the experimental group was exposed to clinical case-based tasks designed to simulate real medical scenarios. The results of pre-test and post-test assessments indicate a substantial improvement in the experimental group, particularly in terms of pragmatic appropriateness and contextual accuracy. The findings suggest that integrating clinical casebased learning into EMP instruction significantly enhances modal competence and bridges the gap between linguistic knowledge and professional communication. The study contributes to linguodidactic theory and provides practical implications for curriculum design in medical education.